Thermally Induced Crosslinking of Poly(N‐Propargyl Glycine). Issue 21 (2nd September 2015) - Secker, Christian; Brosnan, Sarah M.; Limberg, Felix R. P.; Braun, Ulrike; Trunk, Matthias; Strauch, Peter; Schlaad, Helmut
Abstract : As polypeptoids become increasingly popular, they present a more soluble and processable alternative to natural and synthetic polypeptides; the breadth of their potential functionality slowly comes into focus. This report analyzes the ability of an alkyne‐functionalized polypeptoid, poly( N ‐propargyl glycine), to crosslink upon heating. The crosslinking process is analyzed by thermal analysis (differential scanning calorimetry and thermogravimetric analysis), Fourier‐transform infrared, electron paramagnetic resonance, and solid‐state NMR spectroscopy. While a precise mechanism cannot be confidently assigned, it is clear that the reaction proceeds by a radical mechanism that exclusively involves the alkyne functionality, which, upon crosslinking, yields alkene and aromatic products. Abstract : Poly( N ‐propargyl glycine) undergoes crosslinking simply upon heating in the absence of any additives or metal catalysts. The crosslinking process is analyzed by thermal analysis (differential scanning calorimetry and thermogravimetric analysis), Fourier‐transform infrared, electron paramagnetic resonance, and solid‐state NMR spectroscopy.